Comparison of Paraffin Oil Versus Lactulose in Children with Functional Constipation - Hadi, Abdul; Khan, Afzal; Nabi, Muhammad (Indus Journal of Bioscience Research, 2025)
Background: Functional constipation is a common pediatric condition that significantly impacts quality of life. Various laxatives including paraffin oil and lactulose are used for treatment, but comparative efficacy in different demographic groups remains underexplored, especially in resource-limited settings. Objective: To compare the efficacy of paraffin oil and lactulose in children with functional constipation. Study Design: Randomized controlled trial. Duration and Place of Study: Conducted from February 2024 to August 2024 at the Department of Pediatrics, Lady Reading Hospital, Peshawar. Methodology: Sixty children with functional constipation were randomized into two groups of 30 each. Group A received oral paraffin oil, and Group B received oral lactulose, both administered twice daily for eight weeks. Treatment efficacy was assessed based on stool frequency and encopresis episodes recorded by parents during follow-ups at four and eight weeks. Results: Baseline demographics were comparable between groups. Overall efficacy was significantly higher in the paraffin oil group (83.3%) compared to the lactulose group (56.7%) (p=0.047). Stratified analysis revealed paraffin oil’s superior efficacy in younger children (≤6 years), females, and lower socioeconomic and educational backgrounds. Conclusion: Paraffin oil is more effective than lactulose for treating functional constipation in children, particularly in younger age groups and socioeconomically disadvantaged populations, making it a preferred treatment option in similar clinical settings.